O alçamento das vogais médias pretônicas em hinos de folia de reis – Montes Claros/MG - Santos, Cláudia Adriana Souza (2016)
The main objective of this study was to describe and analyze the variable raising of the mid vowels / e / and / o / inpre-stressed position present in the hyms of the Reis Revelry (Folia de Reis) from Montes Claros / MG, in words as d/e/sp/e/dida ~ d[i]sp[i]dida and ass/o/ciação ~ ass[u]ciação, and seek to identify the conditionings that favor the occurrence of the phenomenon that causes the raising among the vowels /e/ ~ /i/ and /o/ ~ /u/. This work was methodologically guided by the Variation Theory precepts proposed by Labov ([1970] 2008). Studies with speech data by Bisol (1981), Viegas (1987), Celia (2004), Viana (2008), Silva (2009), Tondineli (2010), Felice (2012), and writing data by Magalhães (2013) and Bençal (2014) support this dissertation. The linguistic variables considered in the analysis were: previous Context Articulation Mode, previous Context Articulation Point, following Context Articulation Mode, following Context Articulation Point, the stressed syllable vowel Height, stressed vowel Quality, stressed syllable Distance, Type of Syllable, Lexical item. After the orthographic transcription of the hymns, we selected and coded all data relating to the maintenance and to the raising of the mid high vowels /e/ and /o/ in pre-stressed position to finally submit them to GoldVarb X software package. The rounds in the statistical program resulted in a total of 354 occurrences of /e/ and /o/ in pre-stressed syllable, 44 with the performance of [i] and 53 with performance of [u] in this syllable position. The results we obtained showed that in the Reis Revelry from Montes Claros/MG, the raising of the vowels / e / and / o / in pre-stressed position is not priority given by the vowel harmony rule, since the data point out to an evidence of lexical diffusion.